Embodiment of Parental Love Through the Medium of Wooden Matches in Expression Photography - Saputra, Ichsan; Juned, Sulaiman; Nazar, Sahrul (Gondang: Jurnal Seni dan Budaya, 2024)
This photographic work raises the theme of parental love through the medium of wooden matches in expression photography. This work focuses on life experiences, the daily activities of the creator while he was born and grew up full of love from his parents in Aceh. The theory of ideas that the creator uses in creating this work of Expression photography is in the form of Expression Photography, Composition, Semiotics and Lighting. This creation method also involves experimentation. The creative concepts and ideas displayed in this photo work are a reflection of the creator's daily life. The main object in making this work is a miniature person created from wooden matches. This work is inspired by the author's life story of the sincere love of his parents, as well as daily life activities that the author has experienced and felt. Rooted in a deep narrative of parental love, the project captures the essence of familial warmth and affection, depicting miniature wooden matchsticks involved in everyday activities as symbolic representations of the human experience. Each photo encapsulates a narrative of parental love and familial bonds, visually depicting moments of tenderness, joy and nurturing care. In "In Mother's Lap", "Happiness", "Dodaidi Swing", "Adab", and "Guardian", the creator visualizes the multifaceted nature of parental love, from caring for babies to guiding adolescence. These photos are a touching reminder of the eternal bond between parents and children, illustrating the profound impact that love and care can have on a child's development and well-being. Ultimately, through a blend of artistic expression and qualitative inquiry, the project œParental Love through the Medium of Wooden Matching in Expressive Photography transcends the realm of conventional photography, offering viewers a glimpse into the depth and richness of human relationships and experiences.